2015
DOI: 10.1039/c4ra13038c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, light and pH triple stimulated changes in self-assembly of a novel small molecular weight amphiphile binary system

Abstract: Temperature, light and pH induced morphological of C10AZOC2IMB and 4FS binary systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Nevertheless, compared with the stimuli by light (Brown et al, ; Takahashi et al, , ), temperature (Feng et al, ; Jia et al, ), magnetism (Brown et al, , ), CO 2 (Brown et al, ; Ceschia et al, ; Jiang et al, ; Liu et al, ; Scott et al, ; Su et al, ; Zhang & Han, ; Zhang, Zhang, et al, ; Zhu et al, ), and electrochemical redox (Aydogan & Abbott, ; Long et al, ; Rosslee & Abbott, ; Saji et al, ; Sakai et al, ; Tsuchiya et al, ), the redox‐switchable process in this work is hindered by some inherent drawbacks, such as the addition of chemicals (H 2 O 2 and Na 2 SO 3 ) and the by‐product Na 2 SO 4 . Although no obvious deterioration of the response of foaming ability, γ , σ , and θ was observed over 5–10 cycles, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, compared with the stimuli by light (Brown et al, ; Takahashi et al, , ), temperature (Feng et al, ; Jia et al, ), magnetism (Brown et al, , ), CO 2 (Brown et al, ; Ceschia et al, ; Jiang et al, ; Liu et al, ; Scott et al, ; Su et al, ; Zhang & Han, ; Zhang, Zhang, et al, ; Zhu et al, ), and electrochemical redox (Aydogan & Abbott, ; Long et al, ; Rosslee & Abbott, ; Saji et al, ; Sakai et al, ; Tsuchiya et al, ), the redox‐switchable process in this work is hindered by some inherent drawbacks, such as the addition of chemicals (H 2 O 2 and Na 2 SO 3 ) and the by‐product Na 2 SO 4 . Although no obvious deterioration of the response of foaming ability, γ , σ , and θ was observed over 5–10 cycles, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Switchable surfactants (Brown, Butts, & Eastoe, ) can undergo reversible conversion between active (ON state) and inactive (OFF state) forms under particular stimuli, including light (Brown et al, ; Takahashi, Fukuyasu, Horiuchi, Kondo, & Stroeve, ; Takahashi, Koizumi, & Kondo, ), pH (Jia, Cheng, Liu, Li, & Dong, ; Lu, Xue, Wang, & Huang, ; Lv, Qiao, & Xiong, ; Yan et al, ; Zhang, An, & Liu, ), temperature (Feng, Verstappen, Kuehne, & Sprakel, ; Jia et al, ), CO 2 (Brown, Wasbrough, Gurkan, & Hatton, ; Ceschia et al, ; Jiang, Zhu, Cui, & Binks, ; Liu, Jessop, Cunningham, Eckert, & Liotta, ; Scott, Robert, Harjani, & Jessop, ; Su et al, ; Zhang & Han, ; Zhang, Zhang, et al, ; Zhu, Jiang, Cui, & Binks, ), host–guest interactions (Wang, Kang, Tang, & Zhang, ), magnetism (Brown et al, , ), and redox reactions (Aydogan & Abbott, ; Fan et al, ; Long, Tian, Li, & Li, ; Rosslee & Abbott, ; Saji, Hoshino, & Aoyagui, ; Sakai, Imamura, Kondo, Yoshino, & Abe, ; Tsuchiya et al, ). Among the aforementioned stimuli, redox reactions are of particular interest because similar processes (oxygen metabolism) occur constantly in living entities (Fuhrmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the processes with the stimuli of light [6][7][8], temperature [8], magnetism [20,21], CO 2 [2][3][4][14][15][16][17][18], and electrochemical redox reactions [22,23], pH-switchable processes are hindered by inherent drawbacks such as the addition of chemicals and byproducts of inorganic salts. To explore the tolerance toward inorganic salts, the dependence of the pH-switching number on the t 1mL of the C 12 SeO 2 K-based emulsion is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, emulsions that can be emulsified by switchable surfactants [2,3] and/or stimulus-responsive particles [4,5] are switchable. These switchable surfactants and particles have surface activity that can be switched ''on'' or ''off'' upon application of external stimuli such as light [6][7][8], temperature [8], pH [8][9][10][11][12][13], CO 2 [2][3][4][14][15][16][17][18], host-guest interactions [19], magnetism [20,21], and redox reactions [22][23][24][25][26][27]. Because a pH-switchable system is easily prepared at both laboratory and industrial scales, pH is probably one of the most convenient and simplest stimuli, if inherent drawbacks such as the addition of chemicals and byproducts of inorganic salts are not problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Li, Dong, and co‐workers reported multi‐stimuli‐responsive fluids based on an azobenzene‐containing surfactant 1‐[2‐(4‐decylphenylazo‐phenoxy)‐ethyl]‐3‐methylimidazolium bromide (C 10 AZOC 2 IMB) and a hydrotrope 4‐(trifluoromethyl)salicylic acid (4FS) (Figure ). They found that these smart binary systems could be reversibly induced by temperature, light, and pH from vesicles to wormlike micelles 190…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%